The Involvement of Marginalized Menja Society Children in primary education: A case study of the Bench Sheko Zone, Ethiopia - Getachew Gawo, MA; Mebratu Tafesse, PhD (Social Sciences and Humanities Open, 2024)
The study aimed at examining the involvement of marginalized Menja Society Children in primary schools of Bench Sheko Zone. The research utilized a case study design to explore how in-school and out-of-school factors affect the educational participation of Menja Society Children in the Bench Sheko Zone. Qualitative data were collected through interviews, observations, focus group discussions, and document analysis. The snowball sampling technique was used to select informants for the study. The study revealed that factors such as distance, low literacy rates, religious marginalization, economic challenges, limited peer interaction, lack of respect, and unfair treatment are the primary barriers preventing these children from participating in education. Additionally, cultural practices like pot making, agricultural work, and charcoal production also contribute to the marginalization of Menja Society Children. In conclusion, the study underscores the importance of addressing the complex and multi-faceted challenges that marginalized Menja Society Children have been facing in accessing education. The study emphasizes the importance of providing support and resources for Menja children, such as educational materials in their native language and culturally sensitive teachers. It also calls for a comprehensive and collaborative approach to address the educational challenges faced by marginalized Menja Society Children, prioritizing their needs and promoting inclusivity within schools and the wider community. The study recommends creating an inclusive and supportive environment for marginalized students within schools, prioritizing their educational needs, and developing appropriate solutions to ensure equal access to education. It also suggests ongoing awareness campaigns and efforts to promote inter-ethnic relations through various activities. Additionally, providing training for teachers and leaders in cultural diversity and inclusive teaching methods is crucial for establishing a more inclusive learning environment for all Menja children.